2020
DOI: 10.1111/php.13178
|View full text |Cite
|
Sign up to set email alerts
|

Opsin3 Downregulation Induces Apoptosis of Human Epidermal Melanocytes via Mitochondrial Pathway

Abstract: G protein‐coupled receptors (GPCRs) are core switches connecting excellular survival or death signals with cellular signaling pathways in a context‐dependent manner. Opsin 3 (OPN3) belongs to the GPCR superfamily. However, whether OPN3 can control the survival or death of human melanocytes is not known. Here, we try to investigate the inherent function of OPN3 on the survival of melanocytes. Our results demonstrate that OPN3 knockdown by RNAi‐OPN3 in human epidermal melanocytes leads to cell apoptosis. The dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 55 publications
3
45
0
Order By: Relevance
“…In 2020, Wang et al reported that OPN3 is a key receptor responsible for survival of human epidermal melanocytes 59 . They observed that downregulation of OPN3 markedly reduces the intracellular calcium level and triggers the conventional apoptosis pathway via mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Wang et al reported that OPN3 is a key receptor responsible for survival of human epidermal melanocytes 59 . They observed that downregulation of OPN3 markedly reduces the intracellular calcium level and triggers the conventional apoptosis pathway via mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Cytochrome c induces the sequential activation of the caspase cascades, including the activation of caspase9, which then activates downstream caspase3 ( Meng et al, 2012 ; Zhang et al, 2015 ). Different members of the Bcl-2 family of proteins, such as Bax, seem to control the release of cytochrome c ( Wang et al, 2020 ; Yusuf and Casey, 2020 ). Bax plays a role in increasing the permeability of the mitochondrial outer membrane for releasing cytochrome c into the extracorporeal mitochondrial environment ( Ott et al, 2002 ; Pagliari et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAP3K5 is a reliable marker for dominant follicles in cattle, and at day 2.5 post-ovulation there are clear differences in expression of MAP3K5 between the dominant follicle and the next largest follicle a day later [41][42]. Panda et al (2002) concluded that Opn4 is required for light-induced circadian phase shifting, and OPNs play a pivotal role in non-image-forming responses to light, including physiological adaptations to ambient light [43][44]. PIK3R1 plays an important role in regulating ovarian activities in yak seasonal reproduction [45].…”
Section: Discussionmentioning
confidence: 99%